Influence of different types of light on the response of the pulp tissue in dental bleaching: a systematic review - Benetti, Francine [UNESP]; Lemos, Cleidiel Aparecido Araújo [UNESP]; de Oliveira Gallinari, Marjorie [UNESP]; Terayama, Amanda Miyuki [UNESP]; Briso, André Luiz Fraga [UNESP]; Jacinto, Rogério de Castilho [UNESP]; Araújo, Gustavo Sivieri de [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (Springer Nature, 2018)
Objectives: This systematic review (PROSPERO register: CRD42016053140) investigated the influence of different types of light on the pulp tissue during dental bleaching. Materials and methods: Two independent authors conducted a systematic search and risk of bias evaluations. An electronic search was undertaken (PubMed/Medline, Embase, The Cochrane Library, and other databases) until May 2017. The population, intervention, comparison, outcomes (PICO) question was: “Does the light in dental bleaching change the response of the pulp to the bleaching procedure?” The intervention involved pulp tissue/cells after bleaching with light, while the comparison involved pulp tissue/cells after bleaching without light. The primary outcome was the inflammation/cytotoxicity observed in pulp after bleaching. Results: Out of 2210 articles found, 12 articles were included in the review; four were in vivo studies (one study in dogs/others in human), and eight were in vitro studies (cell culture/with artificial pulp chamber or not). The light source used was halogen, light-emitting diode (LED), and laser. Only one in vivo study that used heat to simulate light effects showed significant pulp inflammation. Only two in vitro studies demonstrated that light influenced cell metabolism; one using halogen light indicated negative effects, and the other using laser therapy indicated positive effects. Given that animal and in vitro studies have been identified, there remain some limitations for extrapolation to the human situation. Furthermore, different light parameters were used. Conclusions: The effects of dental bleaching on the pulp are not influenced by different types of light, but different light parameters can influence these properties. Clinical relevance: There is insufficient evidence about the influence of different types of light on inflammation/cytotoxicity of the pulp.
Keywords: Dental bleaching; Light activation; Low-level laser therapy; Pulp inflammation; Systematic review